Valorization of Chicken Feather Keratin as an Eco-Friendly Coagulant for Ochre Dye Removal: A Sustainable Approach - Sri Wahyu Murni; Tutik Muji Setyoningrum; Alim Nurjanah; Sandika Perdana Putra (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This study examines the extraction of keratin from chicken feather waste and its potential use as a coagulant in ochre dye solution treatment. The extraction procedure was investigated for the effect of some parameters, such as temperature (60 – 80 °C), sodium hydroxide concentration (1 – 2 N), and extraction duration (30 – 120 minutes). The maximum keratin yield of 85.64% was obtained using 1.75 N NaOH at 70 °C for 90 minutes. Fourier Transform Infrared spectroscopy confirmed the presence of characteristic protein functional groups in the extracted keratin. Keratin showed modest efficiency as a coagulant in treating the ochre dye solution, with a maximum total solid removal of 47.13% when using a 0.4% keratin dosage-coagulant, pH 10, and 180 minutes of settling time. The study shows that chicken feather waste can be valorized while addressing environmental issues. Nevertheless, additional modification of keratin extraction is required to increase coagulation efficiency, such as considering pH conditions and using an appropriate solvent to minimize keratin degradation.